2021
DOI: 10.29333/iji.2021.14417a
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Factors Affecting Students’ Mathematics Learning Difficulties Using SEM as Information for Teaching Improvement

Abstract: Students' learning math difficulties are influenced by various factors, both internal factors (themselves) and external factors (from outside the students themselves). One of the external factors that can affect student achievement is the campus facilities and infrastructure where they study. This paper aims to estimate structural equation models, which can represent the relationship between latent variables, and the relationship between latent and indicator variables. Besides, it is also to determine which co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…Based on the value of R squared, the variance of endogenous constructions can be explained well by the predictor construction. This model also follows the theory based on the suitability value of the model where the SRMR is less than 0.08 (Elastika et al, 2021;Karwowski et al, 2020). The good reliability of this research data shows that students as respondents and subjects of this study have good consistency.…”
Section: Resultssupporting
confidence: 62%
“…Based on the value of R squared, the variance of endogenous constructions can be explained well by the predictor construction. This model also follows the theory based on the suitability value of the model where the SRMR is less than 0.08 (Elastika et al, 2021;Karwowski et al, 2020). The good reliability of this research data shows that students as respondents and subjects of this study have good consistency.…”
Section: Resultssupporting
confidence: 62%
“…The decision process took into account four essential parts of CFA: loading factor, convergent validity, composite reliability, and discriminant validity. The items, constructs and variables will be consider and accepted as model's elements if the regression weight (β) for factors loading was 0.708 and above, the average variance extracted (AVE) for the convergent validity was 0.5 and above, the composite reliability (CR) value was 0.708 and above, and value of AVE's square root was greater than the inter-correlation values between items or between constructs for discriminant validity (Elastika et al, 2021;Hair et al, 2012;Zainuddin, 2015). Even though the required factor loading value was 0.708 or higher, a regression coefficient of more than 0.4 items was still acceptable if the AVE value was greater than 0.5.…”
Section: International Journal Ofmentioning
confidence: 99%
“…The PCFI and PNFI index values must exceed 0.5 for the fit of the model (Byrne, 2013;Elastika et al, 2021;Ibrahim, Yusof, Morni, et al, 2019;Meyers et al, 2013). If at least one of each category of absolute relative and parsimony indices was fit, the final model was considered fit.…”
Section: The Convergent Validitymentioning
confidence: 99%
“…Various factors can influence the level of student achievement. Ramli et al (2018) and Elastika et al (2021) argued that internal and external factors influence student achievement. Tsai et al (2017) reported that students' learning motivation could predict learning achievement in his research.…”
Section: Introductionmentioning
confidence: 99%